Clinico-etiological profile of neonatal seizures and factors determining outcome in a tertiary referral center of North India - Preeti Sehrawat; Ritu Rakholia; Bindu Deopa; Ankit Kumar (Asian Journal of Medical Sciences, 2025)
Background: Neonatal seizures continue to contribute significantly to neonatal mortality and morbidity in terms of sequelae and cerebral palsy. Aims and Objectives: The objectives of the study were as follows: Study of clinical and etiological profiles of neonates. To study the time of onset of seizures and its relation to etiology and to observe short-term outcomes related to various factors associated with neonatal seizures. Materials and Methods: The study was done to study etiology, onset, type of seizures, and factors determining outcome in a tertiary medical college hospital. It was a prospective observational study enrolling 135 neonates with seizures. History, time of onset, number, type of seizures, examination, and relevant laboratory investigation were documented. Treatment and outcome were documented and analyzed to determine the predictors of outcome. Results: One hundred thirty-five neonates were studied. Neonates were predominantly male (57.7%), term (82.9%), and more than 1.5 kg (93.9%) born by vaginal route (71.8%). Generalized tonic seizures were predominantly seen in 48.14% followed by subtle type (27.40%) and focal tonic type (20.0%). Seizures caused by hypoxic-ischemic encephalopathy (HIE) (45.18%), meningitis (22.96%), metabolic (hypoglycemia [15.55%] and hypocalcemia [6.66%]). HIE, hypoglycemia, intraventricular hemorrhage (IVH), and malformations presented early on day 1 and had a poor prognosis. Meningitis and hypocalcemia presented on day 3–day 7. Metabolic causes had a good prognosis. Multiple (>5) seizures had a poor prognosis. Conclusion: Neonatal seizures had a mortality of 22.9% with HIE having the worst and hypocalcemia best prognosis. Targeted interventions to reduce mortality and morbidity are the need of the hour.